A Book Review of A History of Philosophy: From Bolzano to Wittgenstein - Abdurrazzaq Hesamifar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
A History of Philosophy: From Bolzano to Wittgenstein includes an analytic debate on the most important elements of the ideas of analytic philosophers of the first half of 20th century. The book tries to evaluate and analyze the ideas of analytic philosophers as a philosophical school in philosophy in a way that their ideas can be reduced to each other. After debating on the backgrounds of analytic philosophy, it refers to the ideas of Bolzano, Frege, Russell, early Wittgenstein, Carnap and the movement of formalization and at the end, it shows the ideas of Moore and later Wittgenstein who pursued another way in analytic philosophy which was later known as linguistic philosophy. So, the structure of debate in the book has been directed in two parallel movements, that is, logical analysis and linguistic analysis, though more attention is directed to the first movement. This article goes to assess and criticize the form and the content of the Persian translation of the book.